Development of an Accounting Information System with Data Migration for Company ABC - De Gorostiza, Javi Angela; Nordin, Nur Aidil Bin; Pang, Xin Yi; Sabili, Mark Anthony; Ng, Giuseppe; Mariano, Sol Marian (International Journal of Computing Sciences Research; Vol 1 No 3 (2017): Vol 1, No 3, 2018)
Purpose – The researchers intend to help Company ABC in managing their financial transactions through developing an Accounting Information System (AIS) that would collect, store, and process financial transactions. This system would serve as an instrument needed in the creation of consolidated financial reports for Company ABC, such as Income Statement, Balance Sheet, and Invoices. Method – The methodology for the system development follows Agile methodology. Deliverables would be presented to the client after every sprint to customize the AIS for Company ABC. Results – The Accounting Information System helps the accountants and stakeholders in their decision making process, in enhancing the quality of the financial reports, and in the auditing of financial transactions of the company. Conclusion – With the help of the proposed system, accountants will no longer have a difficult time in creating their reports manually; hence, the proposed system shall help the stakeholders of the company to make sound decisions for the company. Recommendations – To improve its accessibility to its users, it is also recommended that a mobile version of the system that works both in Android and iOS platforms be developed. Research Implications – The use of AIS enables ABC company to collect, store, and process financial transactions into financial reports so as to aid in the decision making and the planning process of the company. However, the implementation of AIS is not an end in itself but rather, a possible important supporting arm to achieve commercial objectives.